Metodologi Penafsiran Tartib Nuzuli al-Jabiri - Said Ali Setiyawan (Farabi, 2016)
This article talks on interpretation methodologhy of tarti>b nuzu>li used by al-Jabiri for understanding al-Qur’an. Al-Jabiri offers new interpretation methodology, tarti>b nuzu>li , for criticizing, completing, and developing previous interpretations which are considered having political, ideoligical motivation, and many importances; and unable to answer many developing modern problems. There are two steps done; He reconstructs definition of al-Qur’an by self referencial and constructs sistematicly methodologycal of al-Qur’an interpretation. They are fas}l al-maqru>’ ‘an al-Qa>ri’ and was}l al-qa>ri’ bi al-maqru>’ whose purposes make al-Qur’an modern for its self (mu’a>s}ra>n li nafsihi> ) and modern for us (mu’a>s}ira>n lana> ). So, the jargon of “s}a>lih} li kulli zama>n wa al-maka>n” can be really applicated without forgetting the authentication of al-Qur’an.